An experimental investigation of indoor bioaerosol dynamics - Muhammad Idris Sulaiman (2017)
Bioaerosols are inborne living microbial particles (Viruses, Fungi or Bacteria) or originate from living micro-organisms. Indoor bioaerosol dynamics differs according to environmental conditions and building materials thus the existence in indoor air is a result of dispersion from various sites of growth or colonization in indoor or outdoor environment. Human activities are main source of microbial penetration however, plants, animals, suspended dust particles, out-door air, temperature and humidity conditions also concern with bioaerosol dynamics. Chapters in this study evaluate the different bioaerosol species including various fungal spores and bacterial species as well as concentration and size of microbial spores. Bacteria and fungi concentrations are higher among all the bioaerosol particles and causing serious implications regarding human health when exposed. Various devices and sampling techniques have been used to identify dispersed species of micro-organisms in the form of colonies, fragments or isolated particles. Analytical studies via flow cytometry, microscopy or cultivation by impingement helps to recognize hazardous particles and penetration source in the built environment that needed to be sustained. The experimental study in last chapter investigates the presence of harmful bacterial and fungal colonies. The main objective is to find a relationship between the bioaerosol concentration and the environmental parameters to see whether any conclusion can be drawn. A properly ventilated system and clean environment can reduce the microbial spore dispersion in indoor areas.